Kolaborasi Project-Based Learning, Deep Learning, dan Media Digital untuk Peningkatan Kemampuan Bernyanyi dan Internalisasi Nilai-nilai Kearifan Lokal Siswa Sekolah Dasar - Desyandri, Desyandri; Mansurdin, Mansurdin; Yeni, Indra; Jannah, Raudhotul (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Music arts learning is not optimal, only focusing on mastering songs imitated by teachers, not utilizing digital technology effectively, and not exploring the values of local wisdom contained in songs are the main factors and urgency of the research. This study describes the improvement of singing skills and internalization of local wisdom values through the collaborative application of the Project Based Learning (PjBL) model, deep learning approach, and multimedia. This study is a Classroom Action Research (CAR) conducted in two cycles with the stages of planning, implementation, observation, and reflection. The subjects of the study were class teachers and 24 fifth-grade students of SD Negeri 11 Padang City. Observers were 3 teachers who had teaching certificates and had more than 10 years of teaching experience. Data collection techniques were carried out through analysis of lesson plans, observations, interviews, learning outcome tests, and singing performance assessments. Data were analyzed using mixed methods, qualitative data using descriptive analysis and quantitative data using percentages and categories. The results of the study showed an increase in: (a) the quality of learning planning from 86.56% to 94.44%, (b) teacher and student activities from 81.93% to 92.59%, and (c) learning outcomes from 77.02 to 88.64. Thus, the combination of the application of the PjBL model, the Deep Learning approach supported by multimedia has proven effective in improving singing abilities, internalizing local wisdom values, thereby strengthening their cultural identity.